Antibody-Free SERS Detection of Severe Fever With Thrombocytopenia Syndrome Virus Using Micron Bowl Array PDMS Substrates - Lin, Ze-Cheng; Lin, Ying-Ting; Tseng, Ching-Yu; Hsu, Wei-Li; Wang, Gou-Jen (IEEE sensors journal, 2025)
Severe fever with thrombocytopenia syndrome (SFTS) is a newly identified zoonotic infectious disease caused by the SFTS virus (SFTSV). For virus prevention and rapid diagnosis, the development of fast and highly sensitive virus detection methods is necessary. In this study, an antibody-free surface-enhanced Raman scattering (SERS) method using novel SERS chips with silver nanoparticles (AgNPs) uniformly deposited on a microbowl array polydimethylsiloxane (PDMS) substrate was proposed for efficient detection of SFTSV. The microbowl array PDMS substrate was fabricated using a nickel mold electroformed through a photolithographically directly written micron bowl array structure of a photoresist template. The SFTSV antigen Gn-mFc was immobilized to the PDMS substrate using the self-assembly monolayer (SAM) method. The experimental results showed that Gn-mFc can be detected in a linear detection range from 87.3 to 8728.5 ng/mL with a limit of detection (LOD) of 51.3 ng/mL. The proposed SERS sensing scheme has the advantages of direct detection (no antibodies and no surface grafting treatment required), small sample usage ( 20~μ L), fast detection (<5 min), and no need for professional operators.